The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/biomedicines10112971
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Workflow of Residual Convolutional Transformer Encoder for Breast Cancer Classification Using Digital X-ray Mammograms

Abstract: Breast cancer, which attacks the glandular epithelium of the breast, is the second most common kind of cancer in women after lung cancer, and it affects a significant number of people worldwide. Based on the advantages of Residual Convolutional Network and the Transformer Encoder with Multiple Layer Perceptron (MLP), this study proposes a novel hybrid deep learning Computer-Aided Diagnosis (CAD) system for breast lesions. While the backbone residual deep learning network is employed to create the deep features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The performance of the DL-based model can also be enhanced by applying data treatment/pre-processing steps, as reported in earlier studies, in many applications, such as for human activity recognition [21], breast cancer classification [22], and dental biometrics [23]. Therefore, in this study, we suggested that applying data preprocessing will help in improving the performance of glaucoma detection/classification.…”
Section: Introductionmentioning
confidence: 66%
“…The performance of the DL-based model can also be enhanced by applying data treatment/pre-processing steps, as reported in earlier studies, in many applications, such as for human activity recognition [21], breast cancer classification [22], and dental biometrics [23]. Therefore, in this study, we suggested that applying data preprocessing will help in improving the performance of glaucoma detection/classification.…”
Section: Introductionmentioning
confidence: 66%
“…Their approach combines attention modules, ASPP, and feature transformer layers into a 3D U-Net architecture, which overcomes the challenges of 3D segmentation, such as varying sizes and low data quality in ABVS data. Al-Tam et al [29] presented a novel hybrid deep learning system for computer-aided diagnosis (CAD) of breast lesions. Their approach combines a residual convolutional network with a transformer encoder that incorporates multiple layer perceptron (MLP) modules.…”
Section: Transformermentioning
confidence: 99%
“…They achieved AUC of 0.784. Al-Tam et al [2] proposed a new hybrid model that involved a transformer encoder with multiple layer perceptron (MLP) for classification based on the high-level deep features extracted via ResNet50. Their proposed model outperformed against others individual classification models of ResNet50, VGG16, and Custom CNN.…”
Section: Vision Transformer-based Medical Image Classificationmentioning
confidence: 99%
“…The model can respond to input from numerous representation subspaces at various locations simultaneously due to the multi-head attention. The multihead attention linearly extends the queries, keys, and values h times using a variety of learnt linear projections, and can be calculated by Equation (2).…”
Section: The Proposed Hybrid Ai Modelmentioning
confidence: 99%
See 1 more Smart Citation